Temperature‐controlled liquid–liquid microextraction combined with high‐performance liquid chromatography for the simultaneous determination of diazinon and fenitrothion in water and fruit juice samples. Issue 11 (3rd April 2018) - Bazmandegan‐Shamili, Alireza; Dadfarnia, Shayessteh; Shabani, Ali Mohammad Haji; Moghadam, Masoud Rohani; Saeidi, Mahboubeh
Abstract: A simple, environmentally benign, and rapid method based on temperature‐controlled liquid–liquid microextraction using a deep eutectic solvent was developed for the simultaneous extraction/preconcentration of diazinon and fenitrothion. The method involved the addition of deep eutectic solvent to the aqueous sample followed by heating the mixture in a 75°C water bath until the solvent was completely dissolved in the aqueous phase. Then, the resultant solution was cooled in an ice bath and a cloudy solution was formed. Afterward, the mixture was centrifuged and the enriched deep eutectic solvent phase was analyzed by high‐performance liquid chromatography with ultraviolet detection for quantification of the analytes. The factors affecting the extraction efficiency were optimized. Under the optimized extraction conditions, the limits of detection for diazinon and fenitrothion were 0.3 and 0.15 μg/L, respectively. The calibration curves for diazinon and fenitrothion exhibited linearity in the concentration range of 1–100 and 0.5–100 μg/L, respectively. The relative standard deviations for five replicate measurements at 10.0 μg/L level of analytes were less than 2.8 and 4.5% for intra‐ and interday assays, respectively. The developed method was successfully applied to the determination of diazinon and fenitrothion in water and fruit juice samples.